Peran Orang Tua dalam memberikan Pendidikan Seks pada Remaja untuk Mencegah Hubungan Seks Pranikah - Inez Dentiana; Adisel Adisel (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
This study aims to understand how the role of parents in providing sex education to adolescents to prevent sex marriage. The research method uses a case study which is a qualitative method that seeks to describe a particular case in greater depth by collecting various sources of information. The results of the study there are factors that empower parents to provide sex education, namely 1). Economic factors, where parents are busy working to earn a living, make parents lack of communication with their children which results in a lack of sex education from parents to children. 2). The factor is the lack of knowledge from parents about sex education, coupled with parents who are still awkward or taboo to discuss sexual issues. The conclusion of this study is that parents have an important role in providing sex education to prevent premarital relationships. Keywords: Parents, Premarital, Sex Education